Organizational Performance and External and Internal Capabilities - NEMA, DR. PRIYANKA (The journal of contemporary issues in business and government, 2021)
While prior research looks at how specific capabilities of companies achieve organizational performance, few studies take a holistic perspective. In this analysis, follow a systemic approach to investigate whether the operational success ultimately accounts for specific capabilities. Also consider how intellectual capital mediates the relationship between the organizational and performance capabilities. In Taiwan Transportation Vehicle research involved a questionnaire study involving 160 executives. Using Structural Equation Modeling (SEM) based on partial least squares (PLS), it was found that business awareness, partnerships, and creative capacities have positive effects on intellectual property, although consumer knowledge has no major impact. Intellectual capital partially mediates the relationship between organizational capacity and performance of the organization. By demonstrating the mediating effects of intellectual capital on the relationships between organizational capacities, both in its external and internal dimensions, and organizational performance, paper contribute to the literature on organizational capabilities, as well as suggesting to companies aiming to enhance organizational performance, particularly those in the transportation sector.